HUBUNGAN RIWAYAT KEKURANGAN ENERGI KRONIK (KEK) PADA IBU DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS KARANG JAYA KABUPATEN MUSI RAWAS UTARA TAHUN 2019 - DEWI APRILIA NINGSIH. I; WAYTHERLIS APRIANI (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2021)
Stunting is a problem that is still considered normal by parents, so this study aims to study the relationship between a history of chronic energy deficiency in mothers with the incidence of stunting in children under five at the Karang Jaya Health Center, Musi Rawas Utara Regency in 2019. This type of research is an analytical survey with a Case Control approach. The population of all toddlers aged 2-5 years 2019 is 103 toddlers. Samples were taken 1: 1, namely 26 people who were stunting were taken by total sampling and 26 people who were not stunted were taken systematically random sampling with a multiple of 3. The data used were secondary data by looking at the documentation. Data analysis was performed using the Chi-Square test (χ2), the Contingency Coefficient test (C) and the Odd Ratio (OR) value. The results showed: (1) Of the 52 samples, 26 people (50%) experienced stunting and 26 people (50%) did not experience stunting; (2) Of the 52 samples, there were 20 people (38.5%) who had a history of KEK and 32 people (61.5%) had no history of KEK and (3) There was a relationship between the history of KEK and the incidence of stunting in children under five in the work area of ​​Puskesmas Karang Jaya North Musi Rawas District, with the category of medium relationship. It is hoped that the Puskesmas will be able to increase public knowledge about the importance of maintaining health during pregnancy by conducting health promotion and direct screening of pregnant women.